Chemical Characteristics and Source Apportionment of Organic Aerosols in Atmospheric PM2.5 in Winter in Beijing - Xu, N.; Wang, T. T.; X. Li; Tang, R. Z.; Guo, S.; Hu, M. (Huanjing Kexue/Environmental ScienceHuanjing Kexue/Environmental ScienceHuanjing Kexue/Environmental Science, 2021)
To explore the concentrations, characteristics, and sources of organic aerosols in winter in Beijing, atmospheric fine particulate matter (PM2.5) samples were collected from November 10, 2016 to December 10, 2016. One hundred and twenty-nine particulate organic matters (POM) were quantified by gas chromatography-mass spectrometry, accounting for approximately 9.3%±1.2% of the total concentration of organic matter. The most abundant class was sugar, among which levoglucosan alone accounted for 18% of the quantified organic matter mass. The next most abundant classes were alkanoic acids, normal alkanes, dicarboxylic acids, and polycyclic aromatic hydrocarbons. The influence of winter heating and biomass burning emissions on organic aerosols in winter in Beijing was analyzed by the characteristics of the molecular markers in the POM. Compared with those during the non-heating period, the concentrations and proportions of hopane species, which are tracers for fossil fuels, increased in the organic matters during the heating period. Moreover, the influence of coal burning emissions on the distribution of hopane species was enhanced. The species with the maximum concentration and carbon predominance index in n-alkanes also reflected the influence of enhanced fossil fuel emissions. The results of the concentration-weighted trajectory model for levoglucosan, a tracer for biomass combustion, suggested that straw burning pollution in the surrounding areas of Beijing would affect the composition of organic aerosols in Beijing via airmass transport. A molecular marker-based chemical mass balance model was used to apportion the sources of organic carbon in the winter of 2016 in Beijing, and the results were compared with those of research in 2006 to quantify the changes in the source contributions over 10 years. The contribution of motor vehicles increased significantly in 2016 compared with that in 2006, whereas the contribution of coal burning and wood burning decreased to a large extent. The contribution of cooking emissions could not be ignored. Therefore, the control of motor vehicle and cooking emissions is of great importance to reduce the problem of PM2.5 pollution in winter in Beijing. © 2021, Science Press. All right reserved.
Keywords: atmospheric aerosols; atmospheric chemistry; Atmospheric fine particulate matter; Beijing; Biogeochemistry; Biomass burning emissions; Chemical characteristic; Chemical mass balance model; coal combustion; fine particulate matter; Fossil fuel emissions; Fossil fuels; Gas chromatography; Gas Chromatography-Mass Spectrometry; mass spectrometry; Maximum concentrations; organic aerosols; Organic carbon; Paraffins; Particles (particulate matter); Particulate organic matters; Pollution control; polycyclic aromatic hydrocarbons; source apportionment; tracers; winter